Gender wage discrimination and trade openness. Prejudiced employers in an open industry - Sarra Ben Yahmed (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
I introduce taste-based discrimination in a trade model with imperfect competition and provide an explanation for the heterogeneous effects of international trade on the gender wage gap within sectors. Firms operate in an oligopoly where prejudiced employers can use their rents to pay men a premium in line with Becker's theory. On one hand, import competition reduces local rents and with them the average gender wage gap in sectors that were sheltered from competition prior to trade liberalization. On the other hand, easier access to foreign markets can increase domestic firms' profits and enable discriminatory firms to maintain wage gaps. Evidence from the Uruguayan trade liberalisation supports the empirical relevance of the taste-based discrimination mechanism at the sectoral level.
urn:nbn:de:bsz:180-madoc-436396
Keywords: F16; J31; J7; L13; 330; gender wage gap; employer taste-based discrimination; international trade; imperfect competition